Local management of second breast cancer event after primary breast conserving therapy: The patient's perspective - Hannoun-Levi, Jean Michel; Margenthaler, Julie; Anderson, Bethany; Di Micco, Rosa; Arthur, Douglas; Aznar, Marianne; Berry, Mary Pat; Brown, Thelma; Burke, Erin; de Boniface, Jana; Dietz, Jill; Dodwell, David; et al. (2025)
BACKGROUND: In case of a second ipsilateral breast cancer event (2ndiBCE) after primary breast conserving treatment (BCT), patients are offered salvage mastectomy (SM) or, for selected patients, 2ndBCT. An international survey dedicated to breast cancer survivors investigated patients' preferences and expectations. METHODS: An international survey was drafted jointly with breast cancer patient advocates from the United States (n = 6) and Europe (n = 2). The survey was validated with 33 questions divided into four themes: demographic data, oncological outcomes, patient views and financial issues. The survey was sent to breast cancer survivors. All information provided was anonymized. RESULTS: From 06/24 to 10/24, 105 patients answered the online survey. The common patient profile was a white (76 %), married (61.5 %), Christian (58.8 %), US-resident (70.2 %) woman aged between 61 and 70 (62.2 %). Long-term outcomes were perceived as being well established for SM (51.5 %) and 2ndBCT (17.1 %). Breast re-irradiation was considered at risk of complications (65.7 %), and 63 % of the patients thought that 2ndBCT provides a more acceptable body self-image. 2ndBCT was expected to give superior cosmetic outcomes than SM with breast reconstruction (55.4 %). Having enough information and ample time to consider the pros and cons of treatment options were very important/important for 99 % and 96.2 %, respectively. Treatment choice was not influenced by financial concerns for 68.3 %. CONCLUSION: Patient perspective is very important in the decision-making process regarding salvage treatments. Physicians must provide clear, timely information which will enable patients to choose the treatment that best meets their expectations.
CRIS-Team Scopus Importer:2025-12-12
Keywords: 2nd breast conserving treatment; Breast cancer; Ipsilateral breast cancer recurrence; Mastectomy; Re-irradiation